Peningkatan Pengetahuan Masyarakat Melalui Pelatihan Pembuatan Minyak Atsiri di Kelurahan Plaju Darat Kota Palembang - Eko Ariyanto; Netty Herawati; Robiah Robiah; Heni Juniar; Dian Kharismadewi (Institut Pertanian Bogor, 2023)
Lemongrass (Cymbopogon citratus) is a family medicinal herb commonly used as a kitchen spice. Lemongrass contains essential oils such as citral, myrcene, geraniol, citronellol, and α-oxo bisabolene that have a high-selling value and benefits as a fungal growth inhibitor, antibacterial, anti-insect, and anti-cancer. Socialization about the benefits of lemongrass essential oils and training on producing its essential oils was conducted through community service. The activity material was delivered through a presentation, and training in processing lemongrass to essential oils was conducted through a demo activity directly in front of participants. This community service activity was held in the Plaju Darat urban village meeting hall involving family welfare empowerment representatives, the head of the neighborhood, and the urban village community as participants. Pre-tests and post-tests were given to participants to determine the level of their understanding of the material presented. The test results improved participants’ understanding of the benefits of essential oils and their processing methods. It was concluded that participants understood the benefits of lemongrass essential oils and knew how to produce them.